2008
DOI: 10.1186/1471-2229-8-95
|View full text |Cite
|
Sign up to set email alerts
|

A first survey of the rye (Secale cereale) genome composition through BAC end sequencing of the short arm of chromosome 1R

Abstract: BackgroundRye (Secale cereale L.) belongs to tribe Triticeae and is an important temperate cereal. It is one of the parents of man-made species Triticale and has been used as a source of agronomically important genes for wheat improvement. The short arm of rye chromosome 1 (1RS), in particular is rich in useful genes, and as it may increase yield, protein content and resistance to biotic and abiotic stress, it has been introgressed into wheat as the 1BL.1RS translocation. A better knowledge of the rye genome c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(92 citation statements)
references
References 40 publications
8
82
0
2
Order By: Relevance
“…It is suggested that retroelements represent more than 50% of the genome of higher plants (SanMiguel et al, 1996), so, it is not surprising to find that 7.5% of the Agave library contains retroelements. Sequencing projects of Daucus carota L. (Cavagnaro et al, 2009), Zea mays (Meyers et al, 2001), Triticum urartu (Akhunov et al, 2005), Pisum sativum (Blemishes et al, 2007) and Secale cereale (Bartos et al, 2008) among others, demonstrated that in these species the retroelements are represented by 56-88%.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that retroelements represent more than 50% of the genome of higher plants (SanMiguel et al, 1996), so, it is not surprising to find that 7.5% of the Agave library contains retroelements. Sequencing projects of Daucus carota L. (Cavagnaro et al, 2009), Zea mays (Meyers et al, 2001), Triticum urartu (Akhunov et al, 2005), Pisum sativum (Blemishes et al, 2007) and Secale cereale (Bartos et al, 2008) among others, demonstrated that in these species the retroelements are represented by 56-88%.…”
Section: Discussionmentioning
confidence: 99%
“…O genoma diploide de trigo é representado por AABBDD (gamético=ABD), enquanto que o de centeio como RR (gamético=R). Este último possui muitos genes de interesse agronômico, dentre eles pode-se citar o Lr26, Yr19, Pm8 e o Sr31, os quais conferem resistência à ferrugem da folha, à ferrugem amarela, ao oídio e à ferrugem do colmo, respectivamente, além de genes que favorecem características agronômicas (KIM et al, 2004;BARTOS et al, 2008).…”
Section: Desenvolvimentounclassified
“…BARTOS et al (2008) estimaram que o segmento 1R possuiria 1.306.781pb de seu genoma composto por elementos repetitivos da Classe I (64,3%), 100.854pb de elementos repetitivos da classe II (5,0%), 30.340pb de elementos não classificados (1,5%), 106.376pb de outras repetições conhecidas (5,2%) e 178.027pb de outras sequências desconhecidas (8,8%). Os mesmos autores identificaram, inclusive, a presença de vários genes no braço curto do cromossomo 1R como do citocromo P450, proteína de reparo por excisão XP-D, isoleucina tRNA ligase, proteína quinase R, MLA I, ACC oxidase, proteína de defesa HCBT, cisteína proteinase e tRNA-HIS guanililtransferase, estimando a presença de 2.000 genes no 1RS e, aproximadamente, 36.000 genes em todo o genoma.…”
Section: Desenvolvimentounclassified
“…Rye is used as a source of resistance genes for many cereal diseases, winter hardiness, tolerance to sprouting, drought, and nutrient deficiencies that can be transferred to closely related cereal crops (Geiger and Miedaner, 2009;Hillel and Rosenzweig, 2005;Wolfe et al, 2008). Compared to wheat and barley, the data available on rye with various sequences collected at gene banks (primarily EST) remains modest (~10,000 sequences) (Bartoš et al, 2008).…”
Section: Introductionmentioning
confidence: 99%